Opinia publiczna w społeczeństwie zinformatyzowanym - Wichura, Jarosław (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Public opinion in the information society Modern developed societies are referred to as information societies. In information societies in the forefront of the industry slip out the acquisition and exploitation of knowledge. Information and knowledge are the most valuable commodity, but also the most dangerous weapon. Virtual, to a large extent, the information society in the end had to take a position on democracy and politics collide with the concept of civil society. The article attempts to characterize the direction of changes that taking place in modern societies in the field of mass media and the public opinion. Author refers to the increasing importance of media in the social, political and economic aspects of human life. Key words: public opinion, information society, new media, Internet